Legal Analysis TikTok Shop Restrictions through Evaluation Minister Trade Regulation No. 31 2023 - Asep Kiki Riady; Otong Syuhada; Herry Farhan Syafiq (Jurisprudentie: Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2025)
This study aims to analyze the legal aspects of restrictions on TikTok Shop in Indonesia through an evaluation of Minister of Trade Regulation No. 31 of 2023. The main focus of this study is to identify the clarity of legal norms governing the social commerce business model, measure the consistency of regulations with the principles of business and consumer protection, and assess the effectiveness of policy implementation in digital trade practices. The method used is a normative legal approach with literature review and case analysis of the closure of TikTok Shop in October 2023 as a concrete illustration of regulatory implementation. The research findings indicate that although these policies are intended to protect the local market and prevent monopolistic practices, there is ambiguity in technical definitions and weak coordination among regulatory agencies, leading to inconsistent implementation. Additionally, the impact on SMEs and consumers highlights the need for more inclusive transition policies and more adaptive legal instruments. This study suggests revising regulations to address the legal challenges posed by technological innovation and to create a fair and sustainable digital trade ecosystem. Keywords: E-commerce, Digital trade regulation, Tiktok shop